Ultrasound-assisted synthesis of unsymmetrical biaryls by Stille cross-coupling reactions - Domini, Claudia Elizabeth (2012)
We describe herein an efficient method for the synthesis of unsymmetrically-substituted biphenyls using a sonochemical variation of the Stille coupling, whose results have also been compared with the conventional silent reaction. Ultrasound significantly enhances this useful organometallic transformation affording products in higher yields and in shorter reaction times than non-irradiated reactions. The scope has been explored with a selection of arylstannanes as precursors and, remarkably, no by-products resulting from homo-coupling could be detected.